Longitudinal 2-year follow-up on the effect of a non-randomised school-based physical activity intervention on reducing overweight and obesity of Czech children aged 10-12 years - Sigmund, Erik; Sigmundová, Dagmar (International journal of environmental research and public health, 2013)
BACKGROUND: This study assessed whether the benefits of a 2-year longitudinal non-randomised school-based physical activity (PA) intervention programme to reduce overweight and obesity were still apparent two years after completion of the controlled intervention. METHODS: The study involved 84 girls (G) and 92 boys (B) aged 10-12 years who had participated in the PA intervention in 2006-2008 as 6- to 9-year olds and were included in the intervention (I) (43 G and 45 B) and the control (C) groups (41 G and 47 B). Participants' overweight/obesity was assessed using the percentile graph of Body Mass Index (BMI) from the World Health Organization for girls and boys aged 5-19. Logistic regression (Enter method) determined the overweight/obesity occurrence in a follow-up measurement (2010) two years after completion of the controlled intervention was used. RESULTS: Two years after the controlled PA intervention had finished, the intervention children were less likely to be overweight/obese than the control children (2.3%GI vs. 17.1%GC, 6.7%BI vs. 23.4%BC, odds ratio: 0.25; 95% confidence interval: 0.12; 0.53; p < 0.001). CONCLUSIONS: The current study indicates favourable effects of an everyday school-based PA intervention programme on lower overweight/obesity incidence, which was maintained two years after the end of the direct involvement of the researchers.
Keywords: logistické modely; podpora zdraví; Female; Overweight; dítě; Health Promotion; ženské pohlaví; Logistic Models; longitudinální studie; Obesity; pohybová aktivita; lidé; školy; následné studie; Schools; Sex Characteristics; Follow-Up Studies; obezita; Male; Czech Republic; pohlavní dimorfismus; index tělesné hmotnosti; nadváha; Česká republika; Motor Activity; Child; mužské pohlaví; Body Mass Index; Longitudinal Studies; Humans